Development of Simple Light Diffraction Props Assisted by Tracker Application with Camera Module and Arduino UNO - Adi Wijaya; Chandra Ertikanto; Doni Andra; Kartini Herlina (STKIP Singkawang, 2022)
This study aims to develop simple light diffraction teaching aids that can be used in learning light diffraction material in schools, as well as to train students' science process skills. This study uses the type of research Design Development and Research (DDR) which is divided into four stages of research, namely analysis, design, development, and evaluation. Before being used in the field, these props were first tested for feasibility. The feasibility test of this light diffraction teaching aid was carried out by conducting a validity test, practicality test, and instrument effectiveness test. In the test results of the validity of teaching aids obtained a percentage of 93% with a very valid category. The results of the practicality test obtained a percentage value of 89% with a very practical category. The results of the test of the effectiveness of teaching aids are represented by the student response test, and the teacher's perception test. In the student response test, a percentage of 86% was obtained in the very effective category, while the teacher perception test obtained a percentage of 84% in the very effective category. Based on the three feasibility tests that have been carried out, it can be concluded that this teaching aid is very suitable to be used in learning diffraction material in schools, and can train students' science process skills.